2014
DOI: 10.1371/journal.pone.0111662
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of and Predictive Factors for Vascular Invasion after Radiofrequency Ablation for Hepatocellular Carcinoma

Abstract: BackgroundVascular invasion in patients with hepatocellular carcinoma (HCC) is representative of advanced disease with an extremely poor prognosis. The detailed course of its development has not been fully elucidated.MethodsWe enrolled 1057 consecutive patients with HCC who had been treated with curative intent by radiofrequency ablation (RFA) as an initial therapy from 1999 to 2008 at our department. We analyzed the incidence rate of and predictive factors for vascular invasion. The survival rate after detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In addition, there were no recognizable local recurrences that could be clearly attributed to the residual tumor at the treatment site. All the patients in this study were treated with hepatic resection, and if they had been treated with local ablation therapy, the prognosis for pathological vascular invasion positive patients might have been poorer than those reported for negative patients . Several previous studies have reported the negative impact of pathological vascular invasion in HCC patients treated with surgical resection .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, there were no recognizable local recurrences that could be clearly attributed to the residual tumor at the treatment site. All the patients in this study were treated with hepatic resection, and if they had been treated with local ablation therapy, the prognosis for pathological vascular invasion positive patients might have been poorer than those reported for negative patients . Several previous studies have reported the negative impact of pathological vascular invasion in HCC patients treated with surgical resection .…”
Section: Discussionmentioning
confidence: 81%
“…The predictive factors for microscopic vascular invasion were evaluated based on age, sex, hepatitis B virus surface antigen (HBsAg), hepatitis C virus antibody (HCVAb), treatment history for HCC, liver damage, tumor number, serum levels of AFP of more than 100 ng/mL, AFP‐L3 of more than 10%, PIVKA‐II of more than 100 mAU/mL, and macroscopic findings. Recurrence‐free and overall survival rates of pathological vascular invasion positive and negative patients were also compared.…”
Section: Methodsmentioning
confidence: 99%
“…Also because of these reasons, many factors and scoring systems evaluated by preoperative noninvasive procedures have been proposed to predict MI‐HCC and/or HCC tumour differentiation . A study by Zhao et al demonstrated that serum AFP level >400 ng/L, serum GGT level >130 U/L, total tumour diameter >8 cm and tumour number >3 were identified as independent predictors of vascular microinfiltration, but this retrospective analysis needs a prospective validation.…”
Section: Discussionmentioning
confidence: 99%
“…2 The 5-year survival rate after vascular invasion development was only 6.4% in our institute. 3 The molecular mechanisms underlying HCC invasion remain ill-defined, hindering the development of novel therapeutic options. Better elucidation of the molecular pathway involved in HCC invasion could facilitate the development of better treatment options for patients.…”
Section: Introductionmentioning
confidence: 99%